Deciphering The Pan-Genome Of Ganoderma sp. To Depict Potential Genomic Components That Contribute To Ganoderma Boninense Pathogenicity - Suhaila Sulaiman; Nur Syamimi Yusoff; Tan Joon Sheong; Lee Yang Ping (Malaysian Society of Applied Biology, 2024)
Volume:47 No:5